Desarrollo de plan de negocios para la creación de una marca de accesorios para mujeres en la ciudad de Quito, que agregue valor a través de diseños exclusivos - Isch Jaramillo, Micaela (2020)
The degree work was carried out in order to determine the commercial and financial viability of creating a women's accessories brand in the city of Quito, which adds value through exclusive designs. The proposed business is within the manufacturing industry, which has presented a growing trend in recent years. The analysis of the Forces of Porter elaborated, suggests a clear opportunity for the implantation of the project in the industry. The market research was carried out through a questionnaire applied to the potential market and two in-depth interviews. The results of the market research confirmed the commercial viability of the proposed business idea. In order to ensure the business construction, a marketing plan was prepared according to the results of the market research, the suggested strategies, resulting from the strategic matrices, and the product life cycle. It was proposed to use a Generic Porter Differentiation Strategy to impact the proposed target market and the value proposition presented, is based on the offer of innovative and personalized designs in everyday items, through which consumers can express their personality. In order to determine the financial viability of the business, a financial plan was developed. The projection of the main financial statements of the project gave a net present value of 11,912.67 dollars and an internal rate of return of 29.94 per cent, concluding that the project is profitable. Based on the analysis carried out, the commercial and financial viability of the proposed business idea was confirmed, therefore its implementation in the market is recommended.